1992
DOI: 10.1007/bf00129880
|View full text |Cite
|
Sign up to set email alerts
|

Telling the tree: Narrative representation and the study of evolutionary history

Abstract: Accounts of the evolutionary past have as much in common with works of narrative history as they do with works of science. Awareness of the narrative character of evolutionary writing leads to the discovery of a host of fascinating and hitherto unrecognized problems in the representation of evolutionary history, problems associated with the writing of narrative. These problems include selective attention, narrative perspective, foregrounding and backgrounding, differential resolution, and the establishment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 15 publications
1
71
0
Order By: Relevance
“…This error does not so much reflect a specific misunderstanding of phylogenetic diagrams per se but a failure to grasp the very concept of common descent. Therefore, the adjustment to be made in this case is from imagining evolution as a linear, progressive process that generates ladder-like ranks to one of branching and diversification of which trees are the result (e.g., O'Hara 1992O'Hara , 1997Nee 2005). …”
Section: Misconception #1: Higher and Lowermentioning
confidence: 99%
“…This error does not so much reflect a specific misunderstanding of phylogenetic diagrams per se but a failure to grasp the very concept of common descent. Therefore, the adjustment to be made in this case is from imagining evolution as a linear, progressive process that generates ladder-like ranks to one of branching and diversification of which trees are the result (e.g., O'Hara 1992O'Hara , 1997Nee 2005). …”
Section: Misconception #1: Higher and Lowermentioning
confidence: 99%
“…Both of these perspectives closely follow the generally Darwinian view that evolution is not much more than a matter of phyletic diversification-"tree-thinking," [22] in the parlance of the period. This is not to suggest that either school of thought depends directly on classical Darwinian views on speciation and the like, but to acknowledge that each does tend to focus on organism-, adaptation-centered, rather than ecologically-centered, outcomes.…”
Section: In His 1972 Work Steps To An Ecology Of the Mind Anthropolomentioning
confidence: 64%
“…Numerous studies have shown that misunderstandings about evolution may either arise from or be perpetuated by how we depict the tree of life when we use it as a visual aid to communication (e.g., O'Hara 1992;Gould 1995;Doolittle and Bapteste 2007). Tree diagrams vary greatly in structure, orientation, and the types of information they depict.…”
Section: Different Ways To Visualize Treesmentioning
confidence: 99%
“…Two main features that communicate these conceptual constraints are related to the overall shape of the tree, and suggest teleology and progress. These features include the trunk of the tree in more naturalistic diagrams (e.g., O'Hara 1992;Gould 1995;Maderspacher 2006;Costa 2009), and upward growth in diagrams that are oriented vertically (Alters and Nelson 2002). These features can to some extent be minimized by changing the orientation of trees, or by teaching students how to interpret them properly (Maddison et al 2007;Gregory 2008).…”
Section: Affordances and Constraints Of Tree Visualizationsmentioning
confidence: 99%